INTERACTION OF CLAY MATERIALS WITH LEAD IN AQUEOUS SOLUTIONS - Kypritidou, Z.; Argyraki, A.; Chryssikos, G.; Stamatakis, M. (Bulletin of the Geological Society of Greece, 2016)
Five bulk clay samples were characterized by XRD, XRF, FTIR and SEM and tested for their effectiveness in removing lead ions from aqueous solutions. These were pal ygorskite, smectite and mixed palygorskite/smectite clays from Macedonia, Greece, as well as a montmorillonite-rich sample from Kimolos, Greece, and a palygorskiterich sample from Western Australia]. Lead removal was investigated as a function of the pH and ionic strength of the suspensions, the amount of sorbent and time, at con stant Pb2+ concentration (50mg/L) and temperature (22oC). The greatest potential fo r Pb2+ removal was found for the natural palygorskite/smectite clay